2022
DOI: 10.3390/polym14235297
|View full text |Cite
|
Sign up to set email alerts
|

Natural Coatings and Surface Modifications on Magnesium Alloys for Biomedical Applications

Abstract: Magnesium (Mg) alloys have great potential in biomedical applications due to their incomparable properties regarding other metals, such as stainless steels, Co–Cr alloys, and titanium (Ti) alloys. However, when Mg engages with body fluids, its degradation rate increases, inhibiting the complete healing of bone tissue. For this reason, it has been necessary to implement protective coatings to control the rate of degradation. This review focuses on natural biopolymer coatings used on Mg alloys for resorbable bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 147 publications
(176 reference statements)
0
5
0
Order By: Relevance
“…Examples of biomedical applications include orthopedic implants, vascular stents, and tissue engineering scaffolds. [86][87][88][89] As an example, cellulose acetate has been explored as a polymeric coating for improving the biocompatibility and corrosion resistance of Mg-based biodegradable implants. One study demonstrated that CA-based composite coatings containing hydroxyapatite (HAp) and Mg particles enhanced the corrosion resistance and hydrophilic characteristics of Mg-based implants.…”
Section: Polymeric Coatingsmentioning
confidence: 99%
“…Examples of biomedical applications include orthopedic implants, vascular stents, and tissue engineering scaffolds. [86][87][88][89] As an example, cellulose acetate has been explored as a polymeric coating for improving the biocompatibility and corrosion resistance of Mg-based biodegradable implants. One study demonstrated that CA-based composite coatings containing hydroxyapatite (HAp) and Mg particles enhanced the corrosion resistance and hydrophilic characteristics of Mg-based implants.…”
Section: Polymeric Coatingsmentioning
confidence: 99%
“…[ 133 ] prepared novel Mg–Ti composites by 3D printing and subsequent acid treatment, which significantly improved the morphology of MC3T3-E1 cells, reduced the apoptosis rate, and enhanced osteogenic activity. Rapid degradation of Mg releases large amounts of hydrogen, which may lead to the separation of tissues and tissue layers, delayed repair of bone defects and tissue necrosis [ 71 , 130 , 134 ]. According to recent studies, the new degradable Mg alloy ZEK100 and tricalcium phosphate coated Mg alloy AZ31 both have good biocompatibility and biodegradability [ 135 , 136 ].…”
Section: Metal Materialsmentioning
confidence: 99%
“…Magnesium alloys have the advantage of light mass and high strength, but they are also more vulnerable to corrosion than other alloys [1][2][3], especially in solutions containing Cland HCO 3 ions [4,5], so anti-corrosion studies for these solutions are key to the protection of magnesium alloys [6,7]. During the preparation of anti-corrosion coatings with magnesium alloys, the composition of the coating produced on the surface will contain magnesium hydroxide if the magnesium alloys are in an alkaline environment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%